ANALISIS PENGARUH INFLASI, KURS, DAN SUKU BUNGA TERHADAP PERGERAKAN BERSAMA RETURN SAHAM IHSG DAN VOLUME PERDAGANGAN PERIODE JANUARI 2006 â€“ DESEMBER 2015 - Kristanto, Muhamad Enggal; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the relationship between stock returns, trading volume and macroeconomic variables such as inflation, exchange rates and interest rates. The endogenous variables in this study are stock returns and trading volume while the exogenous variables are inflation, exchange rates and interest rates. The sample used in this research is secondary data of JCI closing price, trading volume, inflation, exchange rates, and interest rates on the period from 2006 to 2015. Using Eviews 8, methods of analysis used in this study include stationary test, lag order selection criteria, multivariate cointegration tests: Johansen Cointegration Test, VECM estimation, t-statistical tests, F-statistical test, coefficient of determination (RÂ²), impulse response analysis, variance decomposition analysis and granger causality test. The results of this research shows that stock returns have positive effect on trading volume. Trading volume has positive effect on stock returns. Inflation has negative effect on stock returns, but has no effect on trading volume. Exchange rate has no effect both on stock returns and trading volume. Interest rate has no effect both on stock returns and trading volume. Granger causality test shows that there is bi-directional causal relationship between stock returns and trading volume.